The relation of developmental changes in brain serotonin transporter (5HTT) and 5HT1A receptor binding to emotional behavior in female rhesus monkeys: effects of social status and 5HTT genotype - Embree, Molly (2012)
The goal of the present study was to examine how social subordination stress and 5HTT polymorphisms affect the development of brain serotonin (5HT) systems during the pubertal transition in female rhesus monkeys. We also examined associations with developmental changes in emotional reactivity in response to a standardized behavioral test, the Human Intruder (HI). Our findings provide the first longitudinal evidence of developmental increases in 5HT1A receptor and 5HTT binding in the brain of female primates from pre- to peripuberty. The increase in 5HT1A BP(ND) in these socially housed female rhesus monkeys is a robust finding, occurring across all groups, regardless of social status or 5HTT genotype, and occurring in left and right hemispheres of all prefrontal regions studied, as well as amygdala, hippocampus, hypothalamus, and raphe nuclei. 5HTT BP(ND) also showed an increase with age in raphe, anterior cingulate cortex, and dorsolateral prefrontal cortex. These changes in brain 5HT systems take place as females establish more adult-like patterns of social behavior, as well as during the HI paradigm. Indeed, the main developmental changes in behavior during the HI (increase in freezing and decrease in submission/appeasement) were related to neurodevelopmental increases in 5HT1A receptors and 5HTT, because the associations between these behaviors and 5HT endpoints emerge at peripuberty. We detected an effect of social status on 5HT1A BP(ND) in the hypothalamus and on 5HTT BP(ND) in the orbitofrontal cortex, with subordinates showing higher BP(ND) than dominants in both cases during the pubertal transition. No main effects of 5HTT genotype were observed for 5HT1A or 5HTT BP(ND). Our findings indicate that adolescence in female rhesus monkeys is a period of central 5HT reorganization, partly influenced by exposure to the social stress of subordination, that likely functions to integrate adrenal and gonadal systems and shape the behavioral response to emotionally challenging social situations.